Fesyen K-Pop dan Penerapan Syariat Islam di Aceh - Ghufran Aufar Farabi; Hamdani M. Syam (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This research examines the fashion perspectives of K-Pop fans on lifestyle in the USK student environment. Globalization and K-Pop consolidate each other to give birth to new symbols in the fashion world as a form of self-existence, but experience inconsistencies in the application of Islamic law in Aceh. The research method uses a descriptive qualitative approach through the implementation of modeling theory (attention, retention, reproduction, and motivation) with data collection techniques by interview, observation, and documentation of six K-Pop fan informants. The results showed that the perception of fashion materialized through the activity of consuming K-Pop content (Attention) has the effect of following KFashion as an inspiration for fashion dressing (Retention) with innovation and creativity considered to give the impression of simple, cute uniqueness, funny, and not experiencing changes in the fashion cycle so that it is comfortable to use in everyday life even in tropical climates (Reproduction) in the end forming self-existence as a K-Pop fan (Motivation). However, in the application of Islamic fashion, not all K-Fashion is an inspiration to follow. So, it must be acceptability in accordance with the provisions of Islamic teachings in creating K-Fashion using hijab and covering the aurat.